Investigacion de hepatitis b utilizando la técnica inmunocromatografica en trabajadoras sexuales atendidas en el laboratorio del centro de salud nº 6 guano – penipe - Miranda Mata, Patricia Marisol (2010)
Despite the different types of information and security measures that the Ministry of Public Health provides sex workers and the general population is necessary to motivate the monitoring of the spread of various sexually transmitted diseases.